(untitled) (ACTA MEDICA PERUANA, 2024)
In this paper the authors review the experience wlth cholera and pregnancy between 1991-1992 at the María Auxiliadora Hospital (Lima-Perú). During the first year the authors evaluate several factors about cholera and pregnancy, lncluldlng the therapeutlc schedules and other aspects about the management in order to lmprove the morbility and mortallty.